Interdisciplinary Management of a Perforated Aneurysmal Arteria Lusoria: A Case Report - Rouman, Mina; Petrovitch, Alexander; Gey, Eva-Maria; Kuntze, Thomas (The Thoracic and Cardiovascular Surgeon Reports, 2017)
Background An aberrant right subclavian artery (RSA) or arteria lusoria is the most common congenital abnormality of the aortic arch with an incidence of 0.3 to 3.0%.Case Description We report a case of a perforated aneurysmal aberrant RSA, managed using a hybrid approach.Conclusion In emergency cases with acute bleeding, we recommend an endovascular approach to avoid the lethal sequel of arterial leakage. Whenever possible, the pulsatile blood flow to the right arm should be restored. Management should be tailored to the nature of the aneurysmal aberrant RSA, patient's comorbidities, and concomitant lesions.
Keywords: arteria lusoria; aberrant right subclavian artery; aneurysm